2019
DOI: 10.1021/acs.cgd.9b00399
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity in Tetrakis(4-pyridyl)porphyrin Supramolecular Building Blocks

Abstract: In memory of a pioneer in crystal engineering, Prof. Israel Goldberg, we report a series of new framework solids, based on the ligand tetrakis(4-pyridyl)porphyrin (TPyP). Spontaneous reactions of TPyP with seven different metal salts under liquid-liquid diffusion at ambient temperature show that the formation of ionic compounds is preferred to coordination polymers due to increased conformational freedom. Two coordination networks, {(HgI2)2(TPyP)}n•4nCHCl3•2nTCE (TCE = 1,1,2,2-tetrachloroethane), and {(Ba(μ1,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…It provides mostly 1D frameworks with the aid of large connecting metal ions such as Hg 2+ . Rogers et al reported one-dimensional (1D) frameworks for the reaction of HgI 2 with free-base H 2 TPyP in mixed solvents [88]. The network structures consist of tetrahedrally coordinated Hg 2+ cations coordinated with free-base H 2 TPyP ligands to form 1D metallomacrocyclic coordination polymers generated beside the crystallographic c-axis (Figure 9).…”
Section: Pyridyl-based Porphyrinic Mofsmentioning
confidence: 99%
“…It provides mostly 1D frameworks with the aid of large connecting metal ions such as Hg 2+ . Rogers et al reported one-dimensional (1D) frameworks for the reaction of HgI 2 with free-base H 2 TPyP in mixed solvents [88]. The network structures consist of tetrahedrally coordinated Hg 2+ cations coordinated with free-base H 2 TPyP ligands to form 1D metallomacrocyclic coordination polymers generated beside the crystallographic c-axis (Figure 9).…”
Section: Pyridyl-based Porphyrinic Mofsmentioning
confidence: 99%
“…The other ammonium-based cations include organic-functional groups (Di Sipio et al, 1974a,b;Bois et al, 1976a,b;Gatto et al, 2004;Schnaars & Wilson, 2013;Biswas et al, 2017;Serezkhina et al, 2021). Other types of cations that charge-balance (UO 2 Cl 4 ) 2À in the CSD include pyridinium-based (Graziani et al, 1975;Bombieri et al, 1978;Marsh, 1988;Pospieszna et al, 2008;Deifel & Cahill, 2009;Baker et al, 2010;Andrews & Cahill, 2012;Lhoste et al, 2013;Hashem et al, 2013;Surbella III et al, 2016Carter et al, 2018;Mishra et al, 2019;Pyrch et al, 2020), phenanthroliniumbased (Di Sipio et al, 1981, imidazolium-based (Zalkin et al, 1983;Qu et al, 2014;Kohlgruber, 2022), and phosphoniumbased (Brown et al, 1996;Schnaars & Wilson, 2014) species. Other (UO 2 Cl 4 ) 2À complexes have crystallized in the presence of separate metal complexes (Moody & Ryan, 1979;Rogers et al, 1987Rogers et al, , 1990Pons y Moll et al, 2001;Hashem et al, 2014;Falaise et al, 2015;Zhang et al, 2017;Scho ¨ne et al, 2018), crown ethers (Wang et al, 1986;Rogers et al, 1987Rogers & Benning, 1991;Evans et al, 2002) and porphyrins (Mishra et al, 2019).…”
Section: Database Surveymentioning
confidence: 99%
“…[25] By contrast, the 3D columnar layered cMOFs or scMOFs with continuous channels demonstrate high electron transport ability. [26] Particularly, the pillared MOFs synthesized using 5,10,15,20-tetra(4-pyridyl)porphyrin (TPyP) as functional ligand exhibit the adjustable electronic conductivity [27] and structural diversity [28] in light of the features of large planar 𝜋-system, combined electronic properties, chemical reactivity, and structural versatility of TPyP. [29] Consequently, to boost the H 2 production efficiency via the urea-assisted method, it is highly desirable to establish a novel bimetallic pillared scMOFs using TPyP as ligand as the trifunctional electrocatalyst toward the UOR, OER, and HER.…”
Section: Introductionmentioning
confidence: 99%